Gulliver's travels - Swift, Jonathan, 1667-1745 (Oxford world's classics (Oxford University Press), 2005)
"Gulliver's travels purports to be a travel book. It is a blend of fantasy and realism and describes the shipwrecked Gulliver's encounters with the inhabitants of four places: Lilliput, Brobdingnag, Laputa, and the country of the Houyhnhnms"--Provided by publisher.